The Perceived Meanings of Tokopedia Advertisement Video, “Berikan yang Paling Berarti untuk yang Berarti” - L Novelyn (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Delivering a message from an advertisement is important to know whether the message that a company wants to transfer is well-delivered or not because the background of audiences may affect them in interpreting the message. Thus, the writer aims to the writer aims to discover how background education affects people to produce information by observing the perceived meanings produced by English Department respondents and Engineering Department respondents. To do so, the writer uses verbal and non-verbal communications Tokopedia "Berikan yang Paling Berarti untuk yang Berarti" advertisement video. The writer applies Saussure's process of signification and Peirce's three sign mode to analyze the perceived meanings from the respondents. Based on the analysis, the writer discovers all respondents mainly use symbolic mode in producing messages which means the respondents interpret the data by relating it with their personal association. Nonetheless, Engineering Department's respondents use indexical mode more often than English Department's respondents in producing some meanings. Thus, the writer sees that English Department respondents mostly produce moral messages while Engineering Department respondents just mention the storyline. In conclusion, background knowledge indeed affects people to perceive meanings. Keywords: Process of Signification, Perceived Meaning, Verbal and Non-verbal Communication.